2002
DOI: 10.1177/152660280200900411
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Treatment of Symptomatic or Ruptured Abdominal Aortic Aneurysms: The Role of Endovascular Repair

Abstract: EVAR is a feasible treatment in the majority of patients with ruptured or symptomatic AAA. The 30-day mortality appears to be similar between conventionally treated patients and those undergoing endovascular repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 22 publications
0
75
1
1
Order By: Relevance
“…This theory is supported by a Canadian study that, using predictive models, demonstrated improved RAAA mortality following the introduction of an endovascular program. 56 We have also reported several Greenberg et al 8 Hinchliffe et al 9 Veith and Ohki 10 Yilmaz et al 11 Van Herzeele et al 12 Scharrer-Palmer et al 13 Resch et al 14 Lee et al 15 May et al 16 Lombardi et al 17 Arya et al 18 Gerassimidis et al 19 Larzon et al 20 Brandt et al 21 Peppelenbosch et al 22 Alsac et al 23 Hechelhammer et al 24 Vaddineni et al 25 Castelli et al 26 Dalainas et al 27 Oranen et al 28 Greco et al 29 Visser et al 30 Hinchliffe et al 31 Acosta et al 32 Peppelenbosch et al 33 Coppi et al 34 Franks et al 35 Mehta et al 36 The reported mortality rates after endovascular repair vary a great deal in the literature. Useful data can be extracted from 2 registries 56,57 and 4 meta-analyses.…”
Section: Commentmentioning
confidence: 53%
“…This theory is supported by a Canadian study that, using predictive models, demonstrated improved RAAA mortality following the introduction of an endovascular program. 56 We have also reported several Greenberg et al 8 Hinchliffe et al 9 Veith and Ohki 10 Yilmaz et al 11 Van Herzeele et al 12 Scharrer-Palmer et al 13 Resch et al 14 Lee et al 15 May et al 16 Lombardi et al 17 Arya et al 18 Gerassimidis et al 19 Larzon et al 20 Brandt et al 21 Peppelenbosch et al 22 Alsac et al 23 Hechelhammer et al 24 Vaddineni et al 25 Castelli et al 26 Dalainas et al 27 Oranen et al 28 Greco et al 29 Visser et al 30 Hinchliffe et al 31 Acosta et al 32 Peppelenbosch et al 33 Coppi et al 34 Franks et al 35 Mehta et al 36 The reported mortality rates after endovascular repair vary a great deal in the literature. Useful data can be extracted from 2 registries 56,57 and 4 meta-analyses.…”
Section: Commentmentioning
confidence: 53%
“…A similar fluid restriction scheme was reported in 2002 by Veith and Ohki [8] for EVAR in rAAA. Controlled hypotension using vasodilators to lower the blood pressure to <100 mmHg was reported first by our group in 2002 and later by Yilmaz et al [9]. In 2007 Blankensteijn confirmed in a prospective (nonrandomized) study the feasibility of controlled hypotension in candidates for open surgery and endovascular repair.…”
Section: Introductionmentioning
confidence: 80%
“…Reported results of reduced early mortality after EVAR for the treatment of a ruptured AAA compared to open surgery seems conclusive (table 1). However, the currently available, mainly observational, studies are small and add considerable heterogeneity and methodological limitations (Yilmaz et al, 2002;Reichart et al, 2003;Resch et al, 2003;Lee et al, 2004;Alsac et al, 2005;Brandt et al, 2005;Castelli et al, 2005;Hechelhammer et al, 2005;Kapma et al, 2005;Larzon et al, 2005;Vaddineni et al, 2005;Arya et al, 2006;Coppi et al, 2006;Franks et al, 2006;Hinchliffe et al, 2006;Peppelenbosch et al, 2006;Visser et al, 2006;Acosta et al, 2007;Ockert et al, 2007). Heterogeneity is signified by the broad range in percentages of patients treated with EVAR (15-50%) and in percentage of haemodynamical unstable patients (33-73% in the eEVAR group).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of the ruptured AAAs is considered anatomically suitable for eEVAR according to the preoperative CTA scan (Hoornweg et al, 2007). However, logistic problems are often reported which frequently led to the exclusion of EVAR-suitable patients for undergoing endovascular repair (Yilmaz et al, 2002;Reichart et al, 2003;Kapma et al, 2005;Franks et al, 2006;Peppelenbosch et al, 2006;Visser et al, 2006;Acosta et al, 2007). Logistic criteria for EVAR in patients with a ruptured AAA are the instant availability of a CT-scanner, the 24/7 availability of an operating room that is adequately equipped to perform endovascular procedures as well as an endovascular trained staff.…”
Section: Minimally Invasive Endovascular Ruptured Aaa Repairmentioning
confidence: 99%
See 1 more Smart Citation